Love off the leash - Quinn, Tara Taylor (Furever yours., 2022)
"Service dog Jedi is playing...Cupid. As a malnourished rescue dog, I never dreamed Wendy Alvarez would pull me for her Pets for Vets program. Turns out I'm the perfect support animal for ex-vet Greg Martin. Though he insists he's only my "foster," I'm gonna chase Greg's nightmares away and give him the courage to fly his plane again. Plus get him to fall for that nice lady, Wendy. Those loners may be my trainers, but I'm pulling their heartstrings."